CRUSTAL STRUCTURES ACROSS THE ALTYN TAGH FAULT IMAGED BY TELESEISMIC RECEIVER FUNCTIONS AND THEIR GEODYNAMIC IMPLICATIONS - Shi D.; Jiang M.; Yu Q.; Poupinet G.; Herquel G.; Wittlinger G. (My University, 2007)
In the framework of a Sino-French cooperative project 18 three-component portable seismic stations were deployed across the Altyn Tagh fault (ATF) for about five months. From the data recorded on this array, 533 receiver functions with sufficient quality are selected and used in this study. A cross-section about the detailed crustal structures across ATF is then obtained after velocity analysis, common conversion point migration and stacking processes. The Moho discontinuity on the Tarim side is distinctly imaged sub-horizontally at depths of ∼44 km. This discontinuity underthrusts gently and smoothly under the Altyn Tagh to a depth of ∼70 km beneath ATF. The Moho discontinuity south of ATF is also obvious, and distributed sub-horizontally around ∼55 km depth. But, it is heaved up, or "plowed up", by the Tarim lower crust to a depth of ∼45 km near ATF. A fault offset of ∼15 km in Moho is seen approximately under the surface trace of ATF. There is an another phase observed ∼20 km below the Moho in the Tarim basin, which is interpreted to be the compound energies from the multiple converted phases in the sedimentary layer and the directly converted phases of the Hales discontinuity. Our results indicate that ATF is a lithospheric fault, which extends sub-vertically and characterised by a narrow shear zone. Based on these results, we conclude that the lower crust beneath the Tarim basin is more "hard" than that beneath the Qaidam basin. The thickening of Qaidam crust may be partly ascribed to its more "soft" lower crust. The Tibetan plateau can not grow into the Tarim basin is probably simply because the later has more "hard" lower crust and lithospheric mantle. Our results imply that the mechanism of crustal deformation in the northern-most plateau might have some major features outlined in the "hard Tibet" paradigm (Tapponnier et al., 2001) and but also have some other major characters described in the "soft Tibet" paradigm (England and Houseman, 1989; Clark and Royden, 2000).
Keywords: ALTYN TAGH FAULT; CRUSTAL STRUCTURES; RECEIVER FUNCTION; SEISMOLOGY; TIBETAN PLATEAU